Treatment of hypertension by increasing impaired endothelial TRPV4‐KCa2.3 interaction - Dongxu He; Qiongxi Pan; Zhen Chen; Chunyuan Sun; Peng Zhang; Aiqin Mao; Yaodan Zhu; Hongjuan Li; Chunxiao Lu; Mingxu Xie; Yin Zhou; Daoming Shen; et al. (EMBO Molecular Medicine)
Abstract The currently available antihypertensive agents have undesirable adverse effects due to systemically altering target activity including receptors, channels, and enzymes. These effects, such as loss of potassium ions induced by diuretics, bronchospasm by beta‐blockers, constipation by Ca2+ channel blockers, and dry cough by ACEI, lead to non‐compliance with therapies (Moser, 1990). Here, based on new hypertension mechanisms, we explored a new antihypertensive approach. We report that transient receptor potential vanilloid 4 (TRPV4) interacts with Ca2+‐activated potassium channel 3 (KCa2.3) in endothelial cells (ECs) from small resistance arteries of normotensive humans, while ECs from hypertensive patients show a reduced interaction between TRPV4 and KCa2.3. Murine hypertension models, induced by high‐salt diet, N(G)‐nitro‐l‐arginine intake, or angiotensin II delivery, showed decreased TRPV4‐KCa2.3 interaction in ECs. Perturbation of the TRPV4‐KCa2.3 interaction in mouse ECs by overexpressing full‐length KCa2.3 or defective KCa2.3 had hypotensive or hypertensive effects, respectively. Next, we developed a small‐molecule drug, JNc‐440, which showed affinity for both TRPV4 and KCa2.3. JNc‐440 significantly strengthened the TRPV4‐KCa2.3 interaction in ECs, enhanced vasodilation, and exerted antihypertensive effects in mice. Importantly, JNc‐440 specifically targeted the impaired TRPV4‐KCa2.3 interaction in ECs but did not systemically activate TRPV4 and KCa2.3. Together, our data highlight the importance of impaired endothelial TRPV4‐KCa2.3 coupling in the progression of hypertension and suggest a novel approach for antihypertensive drug development.